THE EFFECT OF SWITCHING COST AND PRODUCT RETURN MANAGEMENT ON REPURCHASE INTENT: A CASE STUDY IN THE B2B DISTRIBUTION CHANNEL CONTEXT IN INDONESIA - Lesmono, Stanley Utomo; Santoso, Thomas; Wijaya, Serli; Jie, Ferry (International Journal of Supply Chain Management, 2020)
Business-to-Business (B2B) market normally deals with fewer customers; thus it creates a close relationship between customers and sellers. This relationship must be managed in a way so that it can encourage customer willingness to purchase again. As such, switching cost risk will become less as the customers keep buying from the same channel. At the same time, good return management system also plays an important role for stimulating re-purchase intent in addition to other factors such as customer satisfaction and customer value. This study aimed to analyse the effect of switching cost and product return management on re-purchase intent with customer satisfaction and customer value playing as moderating variables. Company A, a wholesaler that operates in the construction building material business in East Java was selected as the case study object for examining the relationships among the measured concepts. The survey was completed in three cities in which 200 retail stores of Company Aâ??s customers are located The result showed that switching cost and product return management both had a significant effect on retailersâ?? re-purchase intent. Meanwhile, customer value as a moderating variable did not have a significant effect on how switching cost and product return management affecting re-purchase intent. In addition, customer satisfaction had a significant effect on how switching cost influencing re-purchase intent.